Pore flow-through catalytic membrane reactor for steam methane reforming: characterization and performance. Issue 10 (19th July 2022) - Angulo, M.; Agirre, I.; Arratibel, A.; Llosa Tanco, M. A.; Pacheco Tanaka, D. A.; Barrio, V. L.
Abstract : A new reactor configuration with low Pd loadings allows good methane conversion results at low temperatures. Abstract : A series of pore flow-through catalytic nonselective membrane reactors (PTCMRs) were studied for steam methane reforming (SMR) in the 500 to 900 °C temperature range under 10 barg pressure and a steam-to-carbon ratio of 5. The reactants flow through the pores of the membrane where they react on contact with the Pd nanoparticles. Various reactor configurations were prepared and tested with porous α-Al2 O3 -based ceramic tubes with one or more γ-Al2 O3 /YSZ layers on the external surface. The palladium content and dispersion affect the catalytic activity of the reactors and the results show that the efficiency of the reactions depends on the number of γ-Al2 O3 /YSZ layers.